Preparation and Efficacy of Microemulsion Carvacrol-Based Fruit and Vegetable Cleaner and Its Application on Cherry Tomatoes - Yanshuo Wang; Dianjun Sun; Yinghan Zhang; Yichong Zhou; Ruyi Jin; Xiaoli Peng; Jian Li (Foods)
Carvacrol, a natural plant compound with antibacterial, antioxidant, and various biological activities, serves as the basis for developing a micro-emulsion fruit and vegetable cleaner. The study found that carvacrol demonstrated a minimum inhibitory concentration (MIC) ranging between 0.25 and 0.5 mg/mL against four foodborne pathogenic bacteria and three spoilage fungi. The formulated cleaner, containing 67 mg/mL of carvacrol, demonstrated superior characteristics (a particle size of 228 nm, an absolute zeta potential of 21.4 mv, and a stability coefficient of 91.2%). Remarkably, the cleaner remained stable when stored at room temperature for at least 3 months. Its efficacy against pesticides ranged from 76% to 91%. The cleaning effectively inhibited microbial colonies and the decay rate of cherry tomatoes during storage at 4 °C. Furthermore, the cleaning treatment was found to minimize changes in color and hardness. Overall, this study provides evidence that a fruit and vegetable cleaner based on carvacrol enhances the safety of the food industry effectively.